PERANAN LEMBAGA KREDIT INFORMAL BAGI PETANI PADI SAWAH DI DESA WOLAANG KECAMATAN LANGOWAN TIMUR - Rifka Reflin Salangka; Theodora M. Katiandagho; Grace A.J. Rumagit; Lyndon A.J. Pangemanan (Universitas Sam Ratulangi, 2013)
ABSTRACTThe objective of this research is to examine the role ofInformal Credit Institucions for Rice farmers inWolaangVillage Langowan East District and provide benefits, additionalknowledge, information and research is expected to provideinput for the financial management institucions.This research using primary data and secondary data.The sources of primary data are obtained by interviewinglenders and loan recipients by using alist of questions(questionnaire), while the secondary data are taken from theVillage Chief Office. Debtors and creditors sampling had beendone intentionally (purposive sampling) to the 15 debtors and the5 creditors as respondents. Data was analyzed by using tableand Descriptive analyzes.The results of research and discussion showedit that theinformal credit institucions had a role in providing capital forrice farmers in the Wolaang Village Langowan East Districtand made credit process more easy related lending proceduresalthough its interest rate washinger than the formal credit.